Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas XI IPA MA Negeri 1 Lubuklinggau - Maria Luthfiana; Yuliansyah Yuliansyah; Anna Fauziah (Jurnal Pendidikan Matematika:Judika Education, 2018)
The purpose of this study was to determine the effect of problem-based learning models on the mathematical problem solving ability of students of class XI IPA MA Negeri 1 Lubuklinggau. The research method used is true experimental design conducted by the comparison group. The study population was all students of class XI IPA MA Negeri 1 Lubuklinggau, which consisted of 113 students. As an experimental class is class XI Science 3 as many as 36 students and as a control class is class XI Science 2 as many as 38 students selected randomly. Data collection was carried out by means of a descriptive test form. The collected data were analyzed using t-test. Based on the results of the t-test analysis at the significance level α 0.05, obtained (6.80)> (1.671). Conclusion, there is an influence of problem-based learning models on the ability to solve math problems in class XI IPA MA Negeri 1 Lubuklinggau. Keywords: Mathematical Problem Solving Ability, Problem Based Learning.